2022
DOI: 10.1002/mp.15433
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Bremsstrahlung dose in the electron beam at extended distances in total skin electron therapy

Abstract: Electron beam from a linear accelerator is commonly used in total skin electron therapy (TSET) at extended distances. Since Das et al (Med Phys 21, p.1733, 1994 reported 5% bremsstrahlung dose for a 6 MeV electron beam at extended distance of 500 cm it has been accepted as common knowledge. However, measurements by Chen et al (Int J. Rad Onc Biol Phys 59 p.872, 2004) and Monte Carlo simulations by Ding et al (Phys. Med. Biol. 66, 075010, 2021) were unable to reproduce such high bremsstrahlung dose. As bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, a recent study by Ding et al 22 showed that bremsstrahlung dose was < 1% even at SSD = 500 cm and that the common belief of up to 5% bremsstrahlung dose at large extended distances is incorrect. 22 Previously reported high bremsstrahlung doses 21 might be due to poor signal-to-noise ratio for measuring very low dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a recent study by Ding et al 22 showed that bremsstrahlung dose was < 1% even at SSD = 500 cm and that the common belief of up to 5% bremsstrahlung dose at large extended distances is incorrect. 22 Previously reported high bremsstrahlung doses 21 might be due to poor signal-to-noise ratio for measuring very low dose.…”
Section: Discussionmentioning
confidence: 99%
“…showed that bremsstrahlung dose was < 1% even at SSD = 500 cm and that the common belief of up to 5% bremsstrahlung dose at large extended distances is incorrect 22 . Previously reported high bremsstrahlung doses 21 might be due to poor signal‐to‐noise ratio for measuring very low dose 22 . Therefore, the x‐ray contamination to patient is no longer a limiting factor for TSET at large extended distances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations